2018
DOI: 10.3390/ijms19030915
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Respiratory Pathway Component Genes (AOX and ND) in Rice and Barley and Their Response to Stress

Abstract: Plants have a non-energy conserving bypass of the classical mitochondrial cytochrome c pathway, known as the alternative respiratory pathway (AP). This involves type II NAD(P)H dehydrogenases (NDs) on both sides of the mitochondrial inner membrane, ubiquinone, and the alternative oxidase (AOX). The AP components have been widely characterised from Arabidopsis, but little is known for monocot species. We have identified all the genes encoding components of the AP in rice and barley and found the key genes which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 71 publications
2
32
0
Order By: Relevance
“…cDNA of AOX was cloned from highland barley using the candidate gene approach [55]. Comparison with the nucleotide sequences to barley AOXs confirmed that the highland barley AOXs sequences were AOX1 genes.…”
Section: Expression Patterns Of Aox Genes In Highland Barleymentioning
confidence: 88%
“…cDNA of AOX was cloned from highland barley using the candidate gene approach [55]. Comparison with the nucleotide sequences to barley AOXs confirmed that the highland barley AOXs sequences were AOX1 genes.…”
Section: Expression Patterns Of Aox Genes In Highland Barleymentioning
confidence: 88%
“…Phylogenetic analysis has shown the barley AOX ( HvAOX ) family is closely related to the larger AOX gene family in wheat [ 12 ] and, thus, exploring the barley family in order to better understand wheat is a viable endeavor. Similar work has also shown that the rice AOX family ( OsAOX ) contains the AOX1e clade present in wheat, but absent in barley [ 12 , 14 ]. The AOX gene structures, as well as expression patterns have been elucidated in the most recent work in both barley and rice.…”
Section: Introductionmentioning
confidence: 91%
“…While it has been previously shown that HvAOX and OsAOX expression is responsive to stresses and hormones [ 13 , 14 ], their expression levels could also be induced by other factors. There are several positive and negative AOX regulators known to affect expression in the dicot Arabidopsis thaliana .…”
Section: Alternative Oxidase ( Aox ) Regulationmentioning
confidence: 99%
See 2 more Smart Citations